1999
DOI: 10.1002/(sici)1097-0347(199901)21:1<66::aid-hed9>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized bone flaps versus nonvascularized bone grafts for mandibular reconstruction: An outcome analysis of primary bony union and endosseous implant success

Abstract: Background Functional restoration following resection or traumatic injury to the mandible depends on the reliability of the bony reconstruction to heal primarily and support endosseous implants. Although vascularized bone flaps (VBF) and nonvascularized bone grafts (NVBG) are both widely used to reconstruct the mandible, indications for each remain ill‐defined. The purpose of this study was to compare bone graft/flap healing and success of implant placement in patients reconstructed with VBF versus NVBG. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
115
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(122 citation statements)
references
References 12 publications
2
115
0
5
Order By: Relevance
“…5). When deciding to use non-vascularized versus vascularized bone in these types of cases, POGREL et al 30 and FOSTER et al 14 noted an increased complication rate when non-vascularized bone is utilized for treatment of continuity defects greater then 6 cm. POGREL et al recommended avoiding non-vascularized bone when possible in the irradiated patient; it should be reserved for defects less then 6 cm, and adequate intraoral lining is required.…”
Section: Discussionmentioning
confidence: 87%
“…5). When deciding to use non-vascularized versus vascularized bone in these types of cases, POGREL et al 30 and FOSTER et al 14 noted an increased complication rate when non-vascularized bone is utilized for treatment of continuity defects greater then 6 cm. POGREL et al recommended avoiding non-vascularized bone when possible in the irradiated patient; it should be reserved for defects less then 6 cm, and adequate intraoral lining is required.…”
Section: Discussionmentioning
confidence: 87%
“…Shorter periods were found only for the nine removable prostheses as these did not require any healing time for implants. Foster et al (1999) reported considerably shorter times, 10 months, from the reconstruction of jaw continuity until dental restorations were completed. In their study dental implants were, however, already installed in the jaw reconstruction in spite of the risk of improper positioning (Schoen et al, 2004).…”
Section: Time Periods From Jaw Reconstruction To Dental Rehabilitationmentioning
confidence: 99%
“…The introduction of microvascular surgery as an aid in the transplantation of composite grafts has provided the reconstructive surgeon with a means to bridge large bony defects with adequate soft tissue coverage. The success rate of vascularized bone grafting is high and it is the treatment of choice for primary reconstruction 8,22 . Most of the techniques mentioned, however, have their shortcomings in creating an adequate alveolar ridge in which oral implants can be inserted to facilitate prosthodontic rehabilitation.…”
mentioning
confidence: 99%